Economic evaluation in oral health: rehabilitation of a single prosthetic space (Research, Society and Development, 2020)
Objective: To evaluate the allocative efficiency, financial impact, and cost-effectiveness of rehabilitation of a single tooth by means of a 3-unit fixed dental prosthesis and of a dental implant from the perspective of the Commercial Social Service - SESC (“Serviço Social do Comércio”). Methods: An economic analysis of the cost-effectiveness type was designed. A Markov model was developed to capture long-term clinical and economic outcomes considering the temporal horizon of 25 years. Results: Within this temporal horizon it would be possible to perform 308 more procedures with a saving of R$ 351,737.49, if rehabilitation by means of the one-unit implant were chosen. Conclusion: The implant technique with an implant and an implant-supported prosthesis was dominant; that is, it had lower cost and higher effectiveness and its allocative efficiency allowed a much higher number of persons to have access to treatment.